Mountain Food Chains - Royston, Angela, 1945- (Oxford : Raintree, 2015)
This book explores the food chains and webs that exist in a mountain habitat. It equips readers with crucial vocabulary, using examples from that habitat to explain the roles of producers, consumers and decomposers, and illustrates how living things depend upon each other. Readers learn how fragile food chains can be, how they can be broken, and what we can do to prevent this.
First published in hardback in 2014.
Includes bibliographical references and index.
Keywords: Mountain ecology -- Juvenile literature; Food chains (Ecology) -- Juvenile literature; Mountain animals -- Juvenile literature; Wildlife conservation -- Juvenile literature